A new skink of the genus Scincella Mittleman, 1950 (Squamata, Scincidae) from Son La Province, northwestern Vietnam - Anh Van Pham; Thomas Ziegler; Cuong The Pham; Thao Ngoc Hoang; Hanh Thi Ngo; Minh Duc Le (ZooKeys)
A new species of the genus Scincella Mittleman, 1950 is described from northern Vietnam based on morphological and molecular evidence. Scincella truongi sp. nov. is characterized by a combination of the following characters: size medium (SVL up to 59.4 mm); primary temporals 2; external ear opening without lobules; loreals two; supralabials seven or eight; infralabials six or seven; nuchals in three pairs; midbody scales in 28 rows; dorsal scales smooth, in six rows across the back; paravertebral scales 60–67, not widened; ventral scales in 60–70 rows; ten smooth lamellae beneath finger IV and 13–15 beneath toe IV; toes not reaching to fingers when limbs adpressed along body; dorsal surface of body and tail bronze brown with few black spots, a dark stripe running from nostril to eye and extending from posterior corner of eye along upper part of flank to the middle of the tail. In the phylogenetic analyses, the new species is recovered as an independent lineage with no clear sister taxon and at least 17.3% genetic divergence from other species in the genus based on a fragment of the mitochondrial COI gene.